PROBLEMY ZARZĄDZANIA MIEJSCEM ŚWIATOWEGO DZIEDZICTWA UNESCO NA PRZYKŁADZIE PLANU ZARZĄDZANIA DLA KOŚCIOŁÓW POKOJU W JAWORZE I ŚWIDNICY - Waldemar J. Affelt (Ochrona Dziedzictwa Kulturowego, 2017)
A research and educational project “The Churches of Peace in Jawor and Swidnica. World Heritage Site. Management Plan” was carried out between 2012–2014 as part of Polish – German collaboration. It was based upon a textbook published by German Commission for UNESCO. This article presents the principles thereof as well as discusses the results and conclusions coming from the project. Other reference publications dealing with cultural heritage issued after 2014 have been included as well.